Ventilation Requirement for ‘Electric’ Underground Hard Rock Mines – A Conceptual Study - Halim, Adrian; Kerai, M. (The Australasian Institute of Mining and Metallurgy - The AusIMM, 2013)
The electric power price in mining countries such as Australia and South Africa has increased significantly in the past five years and is likely to continue to increase in the foreseeable future. This can make a mine uneconomic to operate. Replacing diesel vehicles with electric ones can reduce ventilation power consumption, which can comprise up to 40 per cent of total mine power consumption. However, no such airflow requirement for electric vehicles is stated in any mining regulations in the world. In this paper, the authors investigate the ventilation requirement of an electric vehicle operating in an underground hard rock mine. Quantification of atmospheric contaminant emitted by an electric vehicle was done at Rio Tinto’s Northparkes mine, followed by thermodynamic and ventilation network simulations using Ventsim Visual software.